m6A mRNA methylation-mediated MAPK signaling modulates the nasal mucosa inflammatory response in allergic rhinitis - Wang, Ruikun; Liang, Jieqiong; Wang, Qian; Zhang, Yiming; Lu, Yingxia; Zhan, Xiaojun; Wang, Shan; Gu, Qinglong (Frontiers in Immunology, 2024)
Background: Allergic rhinitis (AR) is a complex disease in which gene-environment interactions contribute to its pathogenesis. Epigenetic modifications, such as N6-methyladenosine (m6A) modification of mRNA, play important roles in regulating gene expression in multiple physiological and pathological processes. However, the function of m6A modification in AR and the inflammatory response is poorly understood.Methods: We used the ovalbumin (OVA) and aluminum hydroxide to induce an AR mouse model. Nasal symptoms, histopathology, and serum cytokines were examined. We performed combined m6A and RNA sequencing to analyze changes in m6A modification profiles. Reverse transcriptionquantitative polymerase chain reaction (RT-qPCR) and methylated RNA immunoprecipitation sequencing qPCR (MeRIP-qPCR) were used to verify differential methylation of mRNAs and the m6A methylation level. Knockdown or inhibition of Alkbh5 in nasal mucosa of mice was mediated by lentiviral infection or IOX1 treatment.We showed that m6A was enriched in a group of genes involved in MAPK signaling pathway. Moreover, we identified a MAPK pathway involving Map3k8, Erk2, and Nfκb1 that may play a role in the disrupted inflammatory response associated with nasal inflammation. The m6A eraser, Alkbh5, was highly expressed in the nasal mucosa of AR model mice. Furthermore, knockdown of Alkbh5 expression by lentiviral infection resulted in high MAPK pathway activity and a significant nasal mucosa inflammatory response. Our findings indicate that ALKBH5mediated m 6 A dysregulation likely contributes to a nasal inflammatory response via the MAPK pathway.Conclusions: Together, our data show that m6A dysregulation mediated by ALKBH5, is likely to contribute to inflammation of the nasal mucosa via the MAPK signaling pathway, suggesting that ALKBH5 is a potential biomarker for AR treatment.